An analysis of digital marketing and price sensitivity in driving sales: A case study of Ultra Glue - Effendi, Mochamad Salva Putra; Manafe, Leonard Adrie; Nugroho, Dodit Cahyo (Priviet Social Sciences Journal, 2025)
This study examines the role of digital advertising and price in the sales volume of Ultra Glue products in Java, Indonesia. A quantitative approach was applied and data were collected from 50 respondents through a survey. This study evaluates the impact of promotion, price, and sales using multiple regression analysis. The results show that promotion, especially through digital marketing, has a significant impact on sales, which is in line with the literature that recognizes promotional activities as vital in stimulating consumer demand and purchase intention. On the other hand, the impact of price on sales, although positive, is more complex because it is influenced by product quality, overall strategy, and other marketing elements. This study emphasizes the importance of integrated marketing, in which digital promotions are effective, prices are competitive, and products are of good quality to maximize sales. This study also highlights external variables, such as brand loyalty and market competition, to understand consumer behavior in greater depth. We recommend using a blended approach to enrich our understanding of the consumer decision-making process.